Optical characterisation of polymeric nanocomposites using tomographic, spectroscopic and Fraunhofer wavefront assessment - Koukoulas, Triantafillos; Broughton, William R.; Williams, John; Rahatekar, Sameer S. (SPIE - International Society for Optics and Photonics, 2013)
Polymers are often embedded with specific nanofillers such that the functional characteristics and properties of the resulting polymeric nanocomposite (PNC) are enhanced. The degree to which these enhancements can be achieved depends not only on the level of particle loading of nanofillers, but most importantly on the resulting dispersion profile achieved within the matrix. Agglomeration (often referred to as clustering) is a result of the mixing process and very much depends on the chemistry between the polymer and nanofiller. Depending on the PNC type, different mixing processes can be applied but the general consensus is that such processes are not repeatable themselves. Not only it is quite difficult to achieve the desired level of dispersion, but in addition there is a limited number of characterization tools that can be employed to routinely check the homogeneity achieved within a produced sample. Transmission electron microscopy (TEM) and X-ray diffraction (XRD) techniques are usually employed, but they are very time consuming, expensive, require special sample preparation and treatment, often produce results that are difficult to interpret and can only analyse very small areas of sample. This work reports on the adaptation and development and three optical techniques that are non-destructive, can accurately characterize the dispersion achieved as a result of the mixing process and can analyse larger material areas. The techniques reported are based on static and dynamic visible and infra-red light scattering.
Keywords: polymeric nanocomposites; optical coherence tomography; wavefront correlation; photon correlation